The Importance of the Study of Dendrofag Solids in the Fergana Valley - F.Tukhtasinov; D.Sultonov; M.Sodiqova; M.Teshajonova; O.Gafurova (Zien Journals, 2023)
The article describes the important species of dendrophage beetles found in the Fergana Valley, fruit and ornamental trees belonging to 27 families, which are important for their nutrition and survival. Here is a list of 37 species of insects collected and studied from the southern parts of the Fergana Valley. The practical significance of the study of dendrophage solids and ideas on how to increase the effectiveness of the organization of the fight against them are described.
Keywords: dendrophage; fauna; ecological features; ornamental tree